Patient safety culture from the perspective of workers and primary health care teams - Daiane Cortêz Raimondi; Suelen Cristina Zandonadi Bernal; Laura Misue Matsuda (Universidade de São Paulo, 2019)
ABSTRACT OBJECTIVE Analyze if the patient safety culture among professionals in the primary health care differs among health care teams. METHODS Cross-sectional and quantitative study conducted in April and May 2017, in a city in Southern Brazil. A total of 144 professionals who responded to the questionnaire "Survey on Patient Safety Culture in Primary Health Care" participated in the study. Data were analyzed in the Statistical Analysis Software program and expressed in percentage of positive responses. The ethical principles established for research with human beings were applied. RESULTS Patient safety culture is positive among 50.81% of the professionals, and the dimensions "your health service" (63.39%) and "patient safety and quality" (61.22%) obtained the highest average of positive responses. Significant differences were found between the family health and oral health teams (α = 0.05 and p < 0.05), in the dimensions "patient safety" (p = 0.0274) and "work at the health service" (p = 0.0058). CONCLUSIONS We concluded that, although close to the average, patient safety culture among professionals in the Primary Health Care is positive and that there are differences in safety culture between family health and oral health teams in comparison with the primary health care teams.